Faktor-Faktor Yang Berhubungan dengan Perkembangan Balita di Jorong Tabek Kecamatan Pariangan Kabupaten Tanah Datar Tahun 2016 - helpi Nelwatri; Agonwardi Agonwardi; Novantika Dwi Setyanie (STIKes ALIFAH PADANG, 2018)
ABSTRAKGangguan pertumbuhan dan perkembangan pada anak di Indonesia tergolong dalam masalah kesehatan yang tinggi yaitu 35,7% menurut WHO. Diantara faktor yang mempengaruhi perkembangan balita adalah tingkat pengetahuan ibu, pola asuh dan ASI eksklusif. Tujuan Penelitian untuk mengetahui faktor-faktor yang berhubungan dengan perkembangan balita di Jorong Tabek Kecamatan Pariangan Kabupaten Tanah Datar Tahun 2016. Penelitian ini bersifat survei analitik dengan desain cross sectional yang dilaksanakan pada bulan Agustus 2016 – April 2017, sedangkan pengumpulan data dilaksanakan pada tanggal 27 November – 12 Desember 2016 di Jorong Tabek Kecamatan Pariangan Kabupaten Tanah Datar. Populasi adalah seluruh ibu yang mempunyai balita dan balita umur >6 bulan 60 bulan dengan sampel 62 responden. teknik pengambilan sampel Systematic Random Sampling. Instrumen yang digunakan lembar kuesioner. Analisis data univariat dan bivariat yang diolah secara komputerisasi dengan uji statistik chi- square dengan = 0,05. Hasil penelitian didapatkan balita dengan perkembangan menyimpang 1,6%, balita perkembangan meragukan 40,3%, ibu berpengetahuan kurang baik 16,1%, responden yang memberikan pola asuh negatif 47,1% dan ibu yang tidak memberikan ASI eksklusif 56,5%. Dapat disimpulkan ada hubungan tingkat pengetahuan ibu, pola asuh dan pemberian ASI eksklusif dengan perkembangan balita. Diharapkan petugas kesehatan dapat bekerja sama dengan para orang tua dalam meningkatkan kualitas dan kuantitas perkembangan balita dengan memberikan informasi terkait dengan perkembangan balita. ABSTRACT The growth and development disorders on children in Indonesia was categorized in high health problem according to WHO. Some factors that influence the development of toddlers are mother’s level of knowledge, parenting and exclusive breastfeeding. Mothers who have a good knowledge of developments it will assess the development in toddlers, so that each development disorders immediately known. In addition to the need in the physical aspects, education and parenting will also affect to the development of toddlers. Toddlers that getting exclusive breastfeeding is much more mature and better show progression in development compared they are not getting exclusive breastfeeding. This study aims to determine the associated factors with the development of toddlers in Jorong Tabek Pariangan of Tanah Datar district 2016. This research is an analytical survey with cross sectional design. This research was conducted in August 2016-April 2017 and data collection on the November 27th to December 12th, 2016 in Jorong Tabek Pariangan of Tanah Datar district. The population of this research are mothers with toddlers aged > 6 months ≤ 60 months, with a sampel 62 respondent. The sampling technique is systematic random sampling. Instrument used are sheet questionnaire. Univariate and bivariate analyzes of data are processed in a computerized test of chi-square statistic with = 0,05. The Results of this research showed that 1,6% toddlers with deviating development, 40.3% toddlers with dubious development, 16.1% mothers with less knowledgeable, 47.1% of respondents giving negative parenting and 56.5% mother's not giving exclusive breastfeeding. There is significant relationship of mother’s knowledge with development of toddlers (p = 0.005),there is significant relationship of parenting with development of toddlers (p = 0.042) and there is significant relationship of exclusive breastfeeding with development of toddlers (p = 0.020). The conclution of this research showed that there is a significant relationship that mother's knowledge level, parenting and exclusive breastfeeding on development of toddlers. This research expected that health workers make a colaboration with volunteers and the leaders of community to improve the quality and quantity of toddlers development with counseling related to toddlers development it self. Keyword :